Bumiputera accounting students' intention of a professional examination applicability of the theory of reasoned action (TRA) - Abdul Kadir, Dzarfan; Omar, Ropidah; Saad, Sazali (Universiti Utara Malaysia, 2005)
Professional qualification such as Association of Chartered Certified Accountants (ACCA), Institute of Chartered Secretary and Administration (ICSA), Malaysian Institute of Certified Public Accountants (MICPA) and Certified Practicing Accountants Australia (CPA) is important and considered to be added value to the degree possessed by accounting graduates. However there are only small figures of the Bumiputera that possessed such professional qualification. The objectives of the study are to investigate the attitude and subjective norm that influence student’s choice of a professional examination using TRA model and also to study the applicability of TRA in the professional accounting settings. A sample of 86 Bumiputera UUM students from Faculty of Accountancy and completed their practical training been selected for the purpose of data collection. The findings of this study has evidenced that the theory of reasoned action can be applied in professional accounting setting as it can support the study of Bumiputera UUM accounting students’ intention to take professional exam. The strong predictive power of beliefs and attitude in students’ intention to take professional exam was examined and identified.